Perbedaan Jumlah Trombosit Platelet Rich Plasma Yang Menggunakan Tabung Natrium Sitrat Dan Tabung ACD-A - Sheila Clarissa; Jusak Nugraha; Triagung Ruddy (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Background: PRP is a relatively new field and there is still minor researches that are usage. However, PRP can be applied to a lot of various fields. This study willmake a comparison between tubes that have sodium citrate anticoagulant and tubes that have ACD-A anticoagulants, to be able to find out which of the two are able to produce a higher number of PRPs. Objective: To obtain the anticoagulants that produce more platelet countsand to know the difference in the platelet counts in PRPs found in tubes that have sodium citrate anticoagulants and tubes that have ACD-A anticoagulants. Method: This study was an experimental laboratorium research with an equivalent control group design. Data is normally distributed, so that the parametic statistical analysis test uses Paired T-Test. Results: From 32 respondents, there was an increase in both anticoagulant tubes, where the average increase in platelet counts in PRP using sodium citrate tubes was 337593.75 / μl and the standard deviation was 158795.437 whereas, the average increase in platelet counts in PRP using ACD-A tubes was 909062.50 / μL and the standard deviation is. 284336.005. The difference in platelet counts in PRP using sodium citrate tubes and ACD-A tubes was stated to be significant because the result of the Paired T-Test analysis showed Sig (2-Tailed) = 0,000 (p